Characterization of cytochrome P450s (CYP)-overexpressing HepG2 cells for assessing drug and chemical-induced liver toxicity. (29th January 2021) - Chen, Si; Wu, Qiangen; Li, Xilin; Li, Dongying; Mei, Nan; Ning, Baitang; Puig, Montserrat; Ren, Zhen; Tolleson, William H.; Guo, Lei
Abstract: Hepatic metabolism catalyzed by the cytochrome P450 (CYP) superfamily affects liver toxicity associated with exposures to natural compounds and xenobiotic agents. Previously we generated a battery of HepG2-derived stable cell lines that individually express 14 CYPs (1A1, 1A2, 1B1, 2A6, 2B6, 2C8, 2C9, 2C18, 2C19, 2D6, 2E1, 3A4, 3A5, and 3A7). In this study, we comprehensively characterized each cell line for its CYP expression and enzyme activity. Specifically, we measured the mRNA expression, protein expression, and metabolite formation. Using CYP3A4, 2D6, and 2C9-overexpressing cells as representatives, we examined the stability of these cells in long-term cultures for up to 10 passages. The results showed that CYPs can be stably overexpressed for up to 10 cell culture passages without losing their activities. The robustness of responses to stimuli among the cells at different passages was also investigated in CYP3A4-overexpressing cells and the response to amiodarone and dronedarone showed no difference between the cells at the passage 2 and 10. Moreover, the mRNA expression level of most CYPs was higher in CYP-overexpressing HepG2 cells than that in HepaRG cells and primary human hepatocytes. This study confirmed the stability of CYP-overexpressing HepG2 cell lines and provided useful information for a broader use of these cells in pharmacologic and toxicologic research.